Equilibrium and Kinetic Modelling of Phenol Adsorption onto Mixtures of Tar Sands and Titania - Lua'y Zeatoun (Adsorption Science & Technology)
The isotherms and kinetics of adsorption of phenol onto mixtures of physically-activated tar sands and titania were studied at 298 K. Three kinetic models, i.e., pseudo-first order, pseudo-second order and intraparticle diffusion, were applied to fit the experimental data. The best fit was obtained with the pseudo-second-order model. The kinetic parameters were determined to allow the calculation of phenol uptake as function of time. The Langmuir and Freundlich isotherms were employed to determine the adsorption capacities for different initial pH values of the solution. The effects of the particle size of the adsorbent and the initial pH of the solution on the removal of phenol were investigated.